Lumbar spine side bending is reduced in end range extension compared to neutral and end range flexion postures - Ebert, Ryan; Campbell, Amity; Kemp-Smith, Kevin; O'Sullivan, Peter (Churchill Livingstone, 2014)
Lumbar side bending movements coupled with extension or flexion is a known low back pain (LBP) risk factor in certain groups, for example, athletes participating in sports such as hockey, tennis, gymnastics, rowing and cricket. Previous research has shown that sagittal spinal postures influence the degree of spinal rotation, with less rotation demonstrated at end of range extension and flexion. To date it is unknown whether sagittal spinal postures influence side bending. The aim of this study was to determine whether side bend range of motion (ROM) of the lumbar spine is decreased in end-range flexion and extension postures compared to a neutral spine. Twenty subjects between 18 and 55 years of age [mean age = 22.8 yrs (6.8)] with no history of LBP were recruited for this study. Upper (L1–L3) and lower (L3–L5) lumbar side bend, were measured utilising a 14 camera system (Vicon, Oxford metrics, inc.) in end-range flexion, extension and neutral postures, in both sitting and standing positions. The results revealed no statistically significant difference in upper and lower lumbar side bend ROM in an end-range flexion posture compared to a neutral spinal posture. A reduction was found in the range of upper and lower lumbar side bend ROM in an end-range extended posture (p < 0.05), compared to neutral and end range flexion postures. This ROM reduction was found in sitting and standing. These findings allow clinicians to better interpret combined movements involving side bending of the lumbar spine in clinical and real life settings.